Kepribadian Tokoh Utama dalam Novel Sebelas Patriot Karya Andrea Hirata: Kajian Psikoanalisis - Yarta, Abel Hakimi; Nurizzati, Nurizzati; Nst., Bakhtaruddin (Universitas Negeri Padang, 2012)
The purposes of this study were to describe: (1) the personality of Ikal from aspect of Id, (2) personality of Ikal from aspect of Ego, (3) the personality of Ikal from aspect of Superego. The data of this study were the aspect of personality of the main character in this novel. The source of data in this study was the novel Sebelas Patriot by Andrea Hirata. The data were gathered by using descriptive method and technique of reading as well as understanding and identifying the novel of Sebelas Patriot by Andrea Hirata. The finding of this study were: (1) the personality of Ikal from the aspect Id was that there was a desire of Ikal to achieve his father’s dream to be the player of PSSI which could not be reached because of the cruelty of ducth colonization, (2) the personality of Ikal from aspect of Ego was that there was the mitivation of Ikal to train and train himself again in gaining his father’s dream, (3) the personality of Ikal from aspect of Superego was that eventhough the motivation of Ikal to be the player of PSSI could not be achieved, he could still be proud to be the supporter of PSSI. The personality owned by the main character had the balance because Superego had function to relate the demand of Id with Ego, and to live as rational realization.